ROLE OF ARTS AND LITERATURE IN PERSONALITY DEVELOPMENT - Meena, Ramesh Chand; Monika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present research paper is a discussion on an essential area of human life. The personality and its development with art and literature is the focal point of discussion here. Art which includes five dimensions of skill is an integral part of human life. From ancient times man could never escape his life form literature and art. Art works for the inclusion of harmony, rhythm, balance, unity, proportion, love, compassion, sympathy, fluency, compatibility in human life. These qualities lead a man towards a better version of his personality. The area in which art, particularly literature, is most easily demonstrated as an investigatory technique per se is of course that of personality study. Characterization in the master pieces of literary works portrays virtues and follies before reader. The psychological study of human personality is determined by the action of man, but the betterment of these actions can be learnt through art and literature. A writer, painter or sculptor with their artistic impression create classics and leaves the reader, spectator, or art lover to identify and absorb the best rather suitable for one. The formation of personality begins with the birth of a man. It includes songs sung by mother, folk literature in form of mythologies like ‘Ramayana’ and ‘Mahabharata’ or heroic tales of country heroes told by grandparents, folk art forms like ‘mandana’ which is a reflection of cultural perspective of traditions and the whole process seems invisible but before the beginning of any education process lays the foundation of a personality. Man is a social animal and grows in the society. Therefore, the values, believes, experiences and expressions art and literature display belong to that society and reflects the culture of it but for sure makes a man able to transform into a useful human.